Experiment study and refined modeling of temperature field of steel-concrete composite beam bridges. (1st August 2021) - Fan, Jian-Sheng; Liu, Yu-Fei; Liu, Cheng
Highlights: The indoor radiation experiment is carried out for the study of temperature field. A refined model of the solar temperature field of the composite bridge is established. The automatic processing of shadow occlusion effects is realized. The simulated data is in good agreement with the experimental values. The proposed method can realize the temperature analysis of various composite bridges. Abstract: The temperature field and its effect are important issues related to the design and construction of bridges. For steel–concrete composite bridges, the huge difference in thermal performance between steel and concrete makes the temperature field distribution and variation more complicated. In this paper, an indoor baking lamp radiation experiment with controllable parameters is carried out on a group of two steel–concrete composite beam specimens for the study of temperature field. The temperature time-history and distribution laws of the specimen during heating and cooling process are observed and analyzed. Furthermore, a refined numerical model of the solar temperature field of the composite bridge is established and verified by the baking lamp radiation experiment. The proposed refined numerical model of the temperature field of the steel–concrete composite bridge realizes the temperature field analysis of various cross-sections of composite bridges and can automatically consider the shielding effect of the flange on the web, providing a useful tool for the modeling of and analysis of the temperature field of composite bridges.